Lead-Seeking Approaches - Hayward, Matthew M.; Hayward, Matthew M. (Topics in Medicinal Chemistry,, 2010)
Christopher A. Lipinski: Overview of Hit to Lead: The Medicinal Chemist’s Role from HTS Retest to Lead Optimization Hand Off Jeff W. Paslay • John E. Morin • Richard K. Harrison: High Throughput Screening in the Twenty - First Century Jack Andrew Bikker • Lakshmi S.Narasimhan: Lead Discovery Using Virtual Screening Maurizio Pellecchia: NMR Spectroscopy in Fragment Based Drug Design Kevin D. Freeman-Cook • Daniel W. Kung: Hit Triage – Medicinal Chemistry Strategies to Improve the Odds of Success in Discovery John W. Ellingboe • Adam M. Gilbert: Lead Identification.